PENGARUH MEDIA FLASHCARD TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR DITINJAU DARI GENDER - Bela Sintia; Nila Kesumawati; Nugroho Notosutanto Arhon Dhony (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of flashcard learning media on elementary school students' mathematical concept comprehension based on gender. The method used in this study was an experimental method with a posttest-only control group design. The subjects of this study consisted of two fourth-grade classes at SD Negeri 04 Rantau Panjang, namely the experimental class, which was given flashcard learning media, and the control class, which received conventional learning. The instrument used in this study was an essay test to measure students' mathematical concept comprehension abilities. The results of data analysis using a two-way ANOVA test showed that (1) there was a significant effect of flashcard learning media on students' mathematical concept comprehension ability; (2) there was no difference in the average mathematical concept comprehension ability based on students' gender; (3) there was no interaction between flashcard learning media and gender on students' mathematical concept comprehension ability. Thus, flashcard learning media proved to be effective in improving students' mathematical concept comprehension ability without any gender differences